Decrease of Mycoplasma gallisepticum seroprevalence and introduction of new genotypes in Dutch commercial poultry during the years 2001–2018. Issue 1 (2nd January 2021) - ter Veen, C.; Dijkman, R.; de Wit, J. J.; Gyuranecz, M.; Feberwee, A.
ABSTRACT: Almost two decades ago, in addition to a compulsory M. gallisepticum (Mg) monitoring programme of breeding stock based on European Union regulations, the Dutch poultry industry added national regulations to further reduce the Mg prevalence in Dutch commercial poultry. Currently, all commercial chicken and turkey flocks except broilers are monitored for Mg. All breeding flocks on a farm where one or more flocks tested Mg positive are culled. Mg positive layer pullets are channelled and layer pullets placed on Mg positive multi-age farms are vaccinated. The monitoring data obtained were analysed covering a period of 17 years. Moreover, 31 Dutch Mg isolates from the same period were analysed by multilocus sequence typing (MLST) and compared to available PubMLST data. The results show that in breeding stock the seroprevalence decreased from 1.6% to 0.0%, in commercial layers from 6.3% to 1.9%, and in meat turkeys from 17.6% to 2.4%. The MLST results showed the presence of closely related and identical sequence types (STs) within the different Dutch poultry types. Similar STs were found in Northern and Southern Europe only. The results show a fast decline in the Mg prevalence since 2001, although in layers the Mg prevalence has stabilized and suggests backyard poultry might pose a risk for commercial poultry. The need for Mg control across poultry sectors and in trade was confirmed by the similarity in STs found in different types of poultry and regions. These results from the Dutch poultry industry can be extrapolated to Mg control in general.